(untitled) (Third Sector Social Economic Review, 2025)
Ensuring independent audit quality depends on conducting these activities within a certain framework of standardization. Such standardization becomes possible through the effective implementation of Quality Management Standards. However, a review of the literature shows that the extent to which these standards are implemented effectively has not been sufficiently addressed. In this context, the aim of the study is to measure the level at which independent audit firms implement Quality Management Standards and to determine whether these implementation levels show a significant difference according to various demographic and professional variables. The scope of the study consists of 106 independent audit firms operating in Istanbul, including PIEs, and included in the evaluation according to the official registry records of KGK. As a result of the research, it was determined that independent audit firms have a relatively high level of implementation of Quality Management Standards. In addition, it was found that the vast majority of independent auditors have a high level of knowledge regarding Quality Management Standards, and that this knowledge is supported by continuous in-house training. However, the concentration of experience distribution in firms in favor of younger auditors and the relatively low representation of international firms stand out as factors that should be considered regarding the development of the sector. In terms of the sustainability of audit quality, it is understood that emphasis should particularly be placed on the transfer of knowledge and experience from senior auditors to junior auditors and on compliance with global standards. Moreover, it is observed that the level of implementation of Quality Management Standards is largely determined by factors such as experience, authority, internal training, and firm size, whereas variables such as gender, education level, and the sector in which services are provided have a limited effect on this level.